Microbiology with diseases by taxonomy - Bauman, Robert W. (Pearson, 2017)
1. A Brief History of Microbiology2. The Chemistry of Microbiology3. Cell Structure and Function4. Microscopy, Staining, and Classification5. Microbial Metabolism6. Microbial Nutrition and Growth7. Microbial Genetics8. Recombinant DNA Technology9. Controlling Microbial Growth in the Environment10. Controlling Microbial Growth in the Body: Antimicrobial Drugs11. Characterizing and Classifying Prokaryotes12. Characterizing and Classifying Eukaryotes13. Characterizing and Classifying Viruses, Viroids, and Prions14. Infection, Infectious Diseases, and Epidemiology15. Innate Immunity16. Adaptive Immunity17. Immunization and Immune Testing18. Immune Disorders19. Pathogenic Gram-Positive Bacteria20. Pathogenic Gram-Negative Cocci and Bacilli21. Rickettsias, Chlamydias, Spirochetes, and Vibrios22. Pathogenic Fungi23. Parasitic Protozoa, Helminths, and Arthropod Vectors24. Pathogenic DNA Viruses25. Pathogenic RNA Viruses26. Applied and Environmental Microbiology